Terminologia anatomica : international anatomical terminology (Thieme, 1998)
Approved by the International Federation of Associations of Anatomists, this text offers a complete listing of anatomical terms in both Latin and English, with cross-references and an alphabetical index.
Keywords: Terminology as Topic; Anatomy; terminologie jako téma; anatomie